Social Responsibility Practices Regarding Facilities Granted to Employees and Consumer Protection in Selected European Companies - Voicu-Dan Dragomir; Elena Roxana Anghel (Ilcu) (Amfiteatru Economic Journal, 2011)
CSR practices are marked by two essential attributes: their voluntary nature and their extraordinary diversity. In addition, it is difficult to draw the fine line between mere compliance with the law, and those initiatives that exceed the legal requirements, giving social partners a guarantee that companies have actually internalized their social and environmental responsibilities. This article aims to restructure this vast field, following two axes: the facilities granted to employees, on one hand, and consumer protection, on the other hand. In terms of methodology, a sample of the largest 13 listed European companies was selected from as many sectors. The content of annual and sustainability reports issued in 2009, was screened for narrative aspects related to social responsibility, and the material was organized according to the matters voluntarily described by companies. In the area of employment rights, several issues were identified: employee representation on the boards of directors, equal opportunities, professional development, and ethical issues. On the topic of consumer rights, suggestive examples were given on several aspects: healthy products, counseling, after-sales service and customer identity protection. The importance of this research goes beyond these case studies; its originality lies in providing a coherent picture of an area that is perceived as very unstructured. As can be seen from the examples included in this paper, most of the socially responsible initiatives that firms exhibit do not have a negative impact on a firm's profitability, while actually being integrated into products and services as efficiency improvements. Instead, responsible actions can have a major positive impact whenever employees and consumers perceive the company as a fair and generous player who derives profits from the sale of products and services, not in violation of the social partners' rights.
Keywords: M14; M50; D11; 330; corporate social responsibility; facilities granted to employee; consumer protection; European companies